(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article explores the “Belt and Road Initiative” proposed by China as a strategy for establishing economic and trade connections among Asian, European, and African countries. Special attention is given to the commitment to creating a sustainable and innovative “Green Silk Road,” involving collaboration in the fields of ecology and sustainable development. Overall, the “Belt and Road Initiative” is considered as a promising approach to the development of global economic relations, capable of fostering cultural and national convergence.